MTR framework for teaching model-based testing - Németh, Gábor Árpád; Lugosi, Máté István (Teaching Mathematics and Computer Science, 2026)
In the current article, it is presented how Model ≫ Test ≫ Relax (MTR), a free and open-source, extended finite state machine model-based testing framework can be used for education purposes. With the education-related features of MTR – such as graph visualizations, subsequence creation, test suite export – the students are able to understand the concept behind model-based testing, the working of different model conversion and test generation algorithms. With project works, the students use the MTR framework for the automatic test design of a simplified, small scale realworld example. The framework also provides a simulation script for comparing the complexities and fault detection capabilities of different test generation algorithms.Subject Classification: 68M15